2001
DOI: 10.1002/1096-911x(20010101)36:1<251::aid-mpo1062>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Initial characterization of the apoptosis-inducing receptor for natural human anti-neuroblastoma IgM

Abstract: Collectively, our data suggest that NB-p260, the apoptosis-mediating receptor for natural human anti-NB IgM, represents a novel surface protein of human NB cells containing polypeptide sequences related to the subunit c of the mitochondrial ATP synthase and the heat shock protein HSP90.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…31 The target antigen has an apparent molecular mass of 260 kDa and is a surface protein containing polypeptide sequences related to the c subunit of the human mitochondrial ATP synthase and to heat shock protein 90. 32 These IgM antibodies may represent a novel therapeutic tool for neuroblastoma treatment.…”
Section: Tumor Cell Recognition By Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The target antigen has an apparent molecular mass of 260 kDa and is a surface protein containing polypeptide sequences related to the c subunit of the human mitochondrial ATP synthase and to heat shock protein 90. 32 These IgM antibodies may represent a novel therapeutic tool for neuroblastoma treatment.…”
Section: Tumor Cell Recognition By Antibodiesmentioning
confidence: 99%
“…Binding of natural IgM antibodies to neuroblastoma cells induces apoptosis; furthermore, in vivo studies have shown that these antibodies exert potent antitumor activity 31. The target antigen has an apparent molecular mass of 260 kDa and is a surface protein containing polypeptide sequences related to the c subunit of the human mitochondrial ATP synthase and to heat shock protein 90 32. These IgM antibodies may represent a novel therapeutic tool for neuroblastoma treatment.…”
Section: Tumor Cell Recognition By Antibodiesmentioning
confidence: 99%
“…Landmark studies from Rosenberg's group demonstrated that incubation of normal circulating lymphocytes with recombinant (r)IL-2 triggered expansion of the so called "lymphokine activated killer" (LAK) cells, showing HLA-unrestricted cytotoxicity against virtually all tumor targets [78]. Subsequent clinical studies performed in cancer patients using autologous LAK cells associated with rIL-2 proved the therapeutic efficacy of this approach in melanoma and renal cell carcinoma patients, but also its severe toxicity [78].…”
Section: Cytokine Therapy Of Human Neuroblastomamentioning
confidence: 99%